Analisis Kesulitan Mahasiswa dalam Memahami Materi Integral Lipat Dua pada Koordinat Polar Mata Kuliah Kalkulus Lanjut - Apriandi, Davi; Krisdiana, Ika (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This study aims to determine the difficulties experienced by students in understanding the double integral in polar coordinates advanced calculus courses and the factors that cause these problems. This research is qualitative. Subjects were students of the fourth semester of academic year 2015/2016 Mathematics Education, IKIP PGRI Madiun totaling 3 persons. Data collection techniques have used that test, observation, interviews, and documentation. Data analysis technique conducted with qualitative data analysis, namely data reduction, data presentation and conclusion. The results were obtained five kinds of difficulties students in understanding the integral double the coordinates polar, namely 1) the difficulty in drawing a function in polar coordinates and determine the areas of integration, 2) the difficulty in converting the variable into polar coordinates, 3) difficulty in defining the limits of integration, 4) difficulty in writing a form of integration in polar coordinates, 5) difficulties in performing the calculations. Factors causing these difficulties is the ability to understand the matter is low, understanding in drawing a function in two-dimensional and three are still low, difficulties in visualizing the image of a function, do not understand the concept of comparison trigonometry, do not understand in determining the limits of integration in polar coordinates, less rigorous in setting limits of integration, not yet understand the concept of double integral in polar coordinates, lower integration calculation capabilities, yet integral mastered trigonometry.